Comparing the neuropsychological functions in obese and normal people - Ashkani, Sara; Saadatian, Vahid; Rajaei, Ali Reza (Social Determinants of Health, 2021)
Background: Obesity is a chronic heterogeneous disorder causing mental health problems and disorders. This study was aimed at comparing the neuropsychological functions between the obese and normal people. Methods: This study was a descriptive and causal-comparative study conducted on obese and normal people between January and June of 2020. Participants consisted of 100 people (50 obese and 50 normal people) referred to Arian and Saremi clinics in Mashhad. Purposive sampling method was used and the participants were divided into two groups. The instrument was Wisconsin card sorting test (WCST) and Go / No-Go Task. Data were analyzed using SPSS 21 software and multivariate analysis of covariance. Results: The results of the WCST showed that there were no significant differences between the obese and normal people in the variables of neuropsychological functions (P>0.05). Likewise, based on the Go / No-Go homework test, no statistically significant difference was found between the two groups in the variables of neuropsychological functions (P>0.05). Conclusion: The finding showed that there was no difference between neuropsychological functions of the obese and normal people. It can be argued that obesity cannot affect neuropsychological functions.